Predictor of Syncopal Recurrence in Children With Vasovagal Syncope Treated With Metoprolol - Tao, Chunyan; Xu, Bowen; Liao, Ying; Li, Xueying; Jin, Hongfang; Du, Junbao (Frontiers in Pediatrics, 2022)
Objective To explore the predictors for syncopal recurrence in a pediatric population with vasovagal syncope (VVS) treated with metoprolol. Study design This study was conducted retrospectively among children suffering from VVS with or without syncopal recurrence. Data on the detailed medical history and auxiliary examinations were obtained from the electronic medical records. The risk factors for syncopal recurrence were studied by cox regression analyses and the corresponding best cutoff values were determined using receiver operating characteristic analysis. Kaplan-Meier curves were plotted to determine the trends of the syncopal recurrence-free survival rate. Results Forty-two consecutive VVS children were enrolled in the study. At the end of a median follow-up duration of 9.0 (4.8, 19.1) months, 12 patients (29%) experienced  1 syncopal episode. Cox regression analyses revealed that the number of previous syncopal episodes before treatment was a risk factor for syncopal recurrence (hazard ratio = 1.027, 95% confidence interval 1.009 – 1.045, P = .003). Moreover, 4 previous syncopal episodes were certified as the best cutoff value, and the Kaplan-Meier curves showed that the syncopal recurrence-free survival rate over time in patients with > 4 previous syncopal episodes was significantly lower than that in patients with  4 episodes (P = .019 at the log-rank test). Conclusions In a pediatric population with VVS while on the treatment of metoprolol, the number of previous syncopal episodes before treatment played a significant role in predicting syncopal recurrence.